Sol-gel assisted fabrication of collagen hydrolysate composite scaffold: a novel therapeutic alternative to the traditional collagen scaffold - Ramadass, Satiesh Kumar; Perumal, Sathiamurthi; Gopinath, Arun; Nisal, Anuya; Subramanian, Saravanan; Madhan, Balaraman (ACS Applied Materials & Interfaces, 2014)
Collagen is one of the most widely used biomaterial for various biomedical applications. In this Research Article, we present a novel approach of using collagen hydrolysate, smaller fragments of collagen, as an alternative to traditionally used collagen scaffold. Collagen hydrolysate composite scaffold (CHCS) was fabricated with sol-gel transition procedure using tetraethoxysilane as the silica precursor. CHCS exhibits porous morphology with pore sizes varying between 380 and 780 mu m. Incorporation of silica conferred CHCS with controlled biodegradation and better water uptake capacity. Notably, 3T3 fibroblast proliferation was seen to be significantly better under CHCS treatment when compared to treatment with collagen scaffold. Additionally, CHCS showed excellent antimicrobial activity against the wound pathogens Staphylococcus aureus, Bacillus subtilis, and Escherichia coli due to the inherited antimicrobial activity of collagen hydrolysate. In vivo wound healing experiments with full thickness excision wounds in rat model demonstrated that wounds treated with CHCS showed accelerated healing when compared to wounds treated with collagen scaffold. These findings indicate that the CHCS scaffold from collagen fragments would be an effective and affordable alternative to the traditionally used collagen structural biomaterials.
Keywords: collagen; collagen hydrolysate; scaffold; sol-gel; tissue engineering; wound Healing